Karakteristik Kesehatan Reproduksi Pada Janda Usia Sekolah (JUS) di Kecamatan Sumbersari Kabupaten Jember - Pripuspitasari, Dini Eka; Rizki, Rizki; Mauludiyah, Zaida; Octaviani, Yolanda Indri (Riviera Publishing, 2026)
Preparing healthy mothers-to-be is one of the efforts to prevent the birth of stunted babies. However, the number of early marriage incidents in East Java is still high in direct proportion to the high divorce rate, so the ideal of creating healthy mothers-to-be is hampered by the phenomenon of marriage and divorce in adolescence, even at school age which is later known as School-Age Widows (JUS). The results of the 2023 Family Data Collection in East Java show that there are 856 people under the age of 15, while the number of JUS aged 15 to 19 years reaches 2,922 people. Of this figure, Jember Regency is ranked the highest, namely with 189 JUS. This situation will have various effects on women's reproductive health, especially in the situation of adolescent pregnancy which has the potential to become the birth of a stunted baby. Therefore, it is necessary to identify the JUS group to map the current reproductive health status, for the purpose of mapping the right solution in order to prevent the recurrence of adolescent pregnancies that are at risk of giving birth to stunted babies. The population is the entire JUS in Sumbersari District as many as 39 people, while the sample is part of the population of 30 people taken by the purposive sampling method. In this study, the researcher presented the results of the measurement of research data in the form of quantitative data calculated by percentage descriptive technique. The percentage descriptive analysis technique is intended to determine the status of variables, namely to describe reproductive health characteristics related to potential stunting in JUS